Resolução de conflitos socioambientais no Brasil: a utilização dos dispute boards - Zanotto, Letícia Abati (2022)
This Dissertation is part of the Social Relations and Dimensions of Power Research Line and aims to analyze dispute boards and socio-environmental conflicts, in order to observe the use of appropriate means to resolve socio-environmental conflicts. Through an eminently bibliographical research, the main problem is the investigation of the way in which dispute boards can contribute to the resolution of socio-environmental conflicts. Initially, the change in the treatment of the environment in development plans is verified, with international consideration of the need to promote development that is sustainable for the next generations. In terms of national protection, the development of the fundamental right to the environment is another point addressed, with its incorporation through Brazilian constitutions and legislation, with emphasis on the inclusions promoted by CF/88. All foreseen and agreed protection is essential for the preservation of socio-biodiversity and socio-environmental rights. Then, the second chapter works on the appropriate means of conflict resolution, its importance as a method of resolving conflicts before the Judiciary, with a brief description of the construction and functioning of conciliation, mediation and negotiation, with an in-depth look at arbitration and its jurisdiction, as well as the emergence and evolution of dispute boards at the international level. Finally, the development of dispute boards in Brazil, the formation of socio-environmental conflicts and the search for socio-environmental justice are exposed. With this, dispute boards are launched for analysis as a possible appropriate means of resolving socio-environmental conflicts. It is concluded that although it does not cover the entire spectrum that so-called socio-environmental conflicts can assume, it is a tool to be taken into consideration due to its dynamism and preventive nature.